2013
DOI: 10.1039/c3cp44356f
|View full text |Cite
|
Sign up to set email alerts
|

Properties and self-assembled packing morphology of long alkyl-chained substituted polyhedral oligomeric silsesquioxanes (POSS) cages

Abstract: Polyhedral oligomeric silsesquioxane (POSS) cubic cage systems (octa-n-octadecyloctasilsesquioxane, (T8C18) and octakis(n-octadecyldimethylsiloxy)octasilsesquioxane, (Q8C18)) were synthesised with eight long n-alkyl chain (R = C18H37) substituent arms, as model nano-functionalized compounds. The crystalline packing morphology of the cages was studied using time-resolved Small- and Wide-angle X-ray scattering (SAXS/WAXS), thermal and optical techniques. From thermal analysis the melting and crystallization temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 38 publications
5
63
1
5
Order By: Relevance
“…Firstly, looking in detail at the SAXS data which gives information of the long-range ordering and molecular length-scale; Figures 3A and 3B show the 1D SAXS data for the pure POSS materials and the pure PE and PE-POSS blends respectively, where the d-spacings of the peaks are labelled in Angstroms. As previously reported [29,30], the SAXS data for the pure POSS material show very strong 1 st order peaks which have been related directly to the length-scale of the POSS molecule, where the alkylchains point away from the POSS cage core, giving an overall rod-like structure. The POSS molecules pack in an efficient manner in a highly crystalline layered structure, where the alkyl-chains do not interdigitate with each other.…”
Section: X-ray Scattering Datasupporting
confidence: 75%
See 4 more Smart Citations
“…Firstly, looking in detail at the SAXS data which gives information of the long-range ordering and molecular length-scale; Figures 3A and 3B show the 1D SAXS data for the pure POSS materials and the pure PE and PE-POSS blends respectively, where the d-spacings of the peaks are labelled in Angstroms. As previously reported [29,30], the SAXS data for the pure POSS material show very strong 1 st order peaks which have been related directly to the length-scale of the POSS molecule, where the alkylchains point away from the POSS cage core, giving an overall rod-like structure. The POSS molecules pack in an efficient manner in a highly crystalline layered structure, where the alkyl-chains do not interdigitate with each other.…”
Section: X-ray Scattering Datasupporting
confidence: 75%
“…Moreover, we have reported that these particular POSS systems, with long linear alkylchains, pack and crystallize in a lamellar fashion analogous to that of bulk n-alkanes [28][29][30].…”
Section: Thermal Propertiesmentioning
confidence: 98%
See 3 more Smart Citations